Effects of Disaster Management Programs on Individuals' Preparedness in Mount Merapi - Kazuhiko Otani; Djoko Legono; Suseno Darsono; Suharyanto Suharyanto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Disaster management to mitigate or avoid impacts of hazards by reducing vulnerability has been conducted in Mount Merapi since 1969. Vulnerability introduced since 1980s has two main characteristics, such as physical vulnerability (i.e., impacts of hazards) and social vulnerability (i.e., composite characteristics including social, economic and environmental factors). As regulations in Indonesia, i.e. Law of Republic Indonesia No. 24 Year 2007, emphasizes the community involvement in disaster management, individuals or groups of individuals have significant roles in reducing social vulnerability. To promote the community involvement effectively in disaster management, this research hypothesized nine relationships between disaster management programs to assess effects of disaster management programs on the community involvement, such as individuals’ preparedness. Since disaster management programs are not measurable quantitatively, variance-based partial least squares structural equation modeling (PLS-SEM) was applied to test hypothesized causal relationships between the programs. As a result, all nine hypotheses were substantiated. The model revealed that individuals’ preparedness is significantly influenced by emergency logistics and financial aid through self-efficacy, and contingency plans affect reconstruction significantly and successively reconstruction affects rehabilitation.